2016
DOI: 10.1055/s-0036-1584187
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Shape-Memory Alloy Concentrator in Displaced Patella Fractures: Technique and Long-Term Results

Abstract: Operative treatment is usually recommended in displaced patella fractures. Several techniques have been advocated for internal fixation of patella fractures. Despite the relatively good clinical outcomes that have been demonstrated in many studies, postoperative morbidities such as fixation failure, nonunion, infection, and knee stiffness are not uncommon. We present a new alternative treatment technique for displaced patellar fractures. Between April 1995 and May 2005, we used the Nitinol Patella Concentrator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Fortunately, using the patellar concentrator abrogates the need to drill holes in the patella, which avoids the problem of fracture displacement caused by Kirschner wire or screw implantation.In addition,the design of the patellar concentrator conforms to the principle of the tension band, which places continuous pressure on the fracture end [17]. Hence, the patellar concentrator possesses advantages of both simple operation and early functional exercise, and is suitable for various types of patellar fractures [5,10].However, our results revealed that the patellar concentrator alone produces poor reduction of the inferior patellar pole fracture. Lateral comminuted fractures were earlier shown to be di cult to x with patellar concentrator alone [18], so multiple C-arm uoroscopies are needed to ensure proper reduction.…”
Section: Discussionmentioning
confidence: 80%
“…Fortunately, using the patellar concentrator abrogates the need to drill holes in the patella, which avoids the problem of fracture displacement caused by Kirschner wire or screw implantation.In addition,the design of the patellar concentrator conforms to the principle of the tension band, which places continuous pressure on the fracture end [17]. Hence, the patellar concentrator possesses advantages of both simple operation and early functional exercise, and is suitable for various types of patellar fractures [5,10].However, our results revealed that the patellar concentrator alone produces poor reduction of the inferior patellar pole fracture. Lateral comminuted fractures were earlier shown to be di cult to x with patellar concentrator alone [18], so multiple C-arm uoroscopies are needed to ensure proper reduction.…”
Section: Discussionmentioning
confidence: 80%
“…However, the TNSMPC can fix the fracture independently by its claws and causes no extra bone loss, which can achieve excellent outcomes in osteoporotic or comminuted cases. The study conducted by Yutong Zhang et al, described another similar patella concentrator and reported desired outcomes in pole fracture or comminuted patella fractures [ 21 ]. Fracture displacement due to the loosening of the claw is a potential complication of the operation while it did not happen in cases with comminuted fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Yutong Zhang et al described another similar patellar concentrator and report desired outcomes in pole fracture or comminuted patellar fractures. [21] Fracture displacement due to the loosening of the claw is potential complications of the operation while it did not happen in cases with comminuted fractures. Figure 5 shows the failure of the internal fixation in a case with a simple transverse fracture and the revision surgery was performed by removing the screws, reducing the fracture and fixing it with the claw and additional circle wire.…”
Section: Follow-up Assessmentmentioning
confidence: 99%